2015
DOI: 10.1038/srep12486
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable magnesium-ion battery based on a TiSe2-cathode with d-p orbital hybridized electronic structure

Abstract: Rechargeable ion-batteries, in which ions such as Li+ carry charges between electrodes, have been contributing to the improvement of power-source performance in a wide variety of mobile electronic devices. Among them, Mg-ion batteries are recently attracting attention due to possible low cost and safety, which are realized by abundant natural resources and stability of Mg in the atmosphere. However, only a few materials have been known to work as rechargeable cathodes for Mg-ion batteries, owing to strong elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
156
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 52 publications
7
156
0
Order By: Relevance
“…Lastly, Gu et al [172] obtained similar results for VSe 2 as compared to TiSe 2 . With a major discharge plateau slightly below 1 V and a capacity of ~110 mA h g −1 , over 60 cycles were demonstrated with no apparent capacity fading.…”
Section: Science China Materialssupporting
confidence: 71%
See 1 more Smart Citation
“…Lastly, Gu et al [172] obtained similar results for VSe 2 as compared to TiSe 2 . With a major discharge plateau slightly below 1 V and a capacity of ~110 mA h g −1 , over 60 cycles were demonstrated with no apparent capacity fading.…”
Section: Science China Materialssupporting
confidence: 71%
“…In agreement with Liang et al [166], they point to tuning the interlayer spacing as a useful tool. However, they also note that the ease with which transition metals change valence states plays an important role in determining the diffusion barrier for Mg, which may preclude TiS 2 Gu et al [172] recently reported on TiSe 2 for the first time as an MIB cathode material. Noting the beneficial effects of electron delocalization in CP [100], the study focused on hybridization of the energetically similar Ti 3d and Se 4p atomic orbitals (Fig.…”
Section: Science China Materialsmentioning
confidence: 99%
“…Gu et al. reported that the d‐p orbital hybridization in TiSe 2 is a possible key factor to realize reversible intercalation of Mg 2+ into TiSe 2 . As inspired by all these previous reports, TiSe 2 nanosheets are expected to be promising electrode materials for SIBs.…”
Section: Introductionmentioning
confidence: 95%
“…The strong Coulomb interaction between Mg 2+ and host lattice prevents fast ion diffusion in solid-state electrodes [9], as well as the high coordinating ability of Mg 2+ ion to hard Lewis bases such as N-and O-containing functional groups. Compared to Li-ion batteries, only a few kinds of transition metal compounds, such as Chevrel phase (Mo 6 X 8 , X = S, Se) [10,11], oMo 9 Se 11 [12], MX 2 (M = Ti, Mo, W, X = S, Se) [13][14][15][16], TiS 3 [17], MgMSiO 4 (M = Fe, Mn, Co) [18][19][20], MgFePO 4 F [21], and MnO 2 [22,23], have been reported as insertion-type cathodes for Mg batteries. It is noteworthy here that these cathode materials were basically chosen from a viewpoint that Mg 2+ ions could be inserted into, and extracted from, void space of the host lattices; this type of compounds was, however, extremely limited at present.…”
Section: Introductionmentioning
confidence: 99%